Design of ABS Pneumatic Brake Simulation Tool Arduino Based - Nur Hidayat; Hamid Hamid (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
The simulation of the pneumatic antiloc brake system (ABS) is a system on the vehicle that functions to prevent the wheels from locking during sudden braking. The application of the antilock brake system is still limited to certain vehicles because the price is quite expensive. For this reason, a study on the ABS brake simulation system was carried out to find out how the pneumatic brake system works. The addition of ultrasonic sensor components that are controlled through arduino ABS is poured into the design of the ABS pneumatic brake system (antilockbrakesystem). This test was carried out to determine the ultrasonic sensor control as an automatic control of the brake with a variation in the distance set on the arduino microcontroller brake control (200 cm, 100 cm) performs air solenoid control as a braking trigger in the condition before, during and after braking. The research was conducted looking at the control of the Arduino application monitor. From the results of the study, it was obtained that the addition of ultrasonic sensor components to the condition when the vehicle has obstacles or obstacles to brake work automatically which often occurs in urban areas. The system is carried out using ultrasonic trigger work. From this data, the ABS braking system works according to the ABS braking system settings that rely on ultrasonic distance resistance to produce medium to full valve closure commands.